Prediction of Sanchez-Lacombe equation of state characteristic parameters for plus fractions - Sadat-Shojaei, A.; Khorsand Movaghar, M.; Mousavi Dehghani, Seyed Ali (Wiley-Blackwell Publishing, 2015)
© 2015 Canadian Society for Chemical Engineering. Sanchez-Lacombe is one of the main polymeric equations of state that is used to predict thermodynamic properties of polymer solutions. Due to the similarity of the physical behaviour of polymer solutions and black oil, Sanchez-Lacombe is also recommended to predict the liquid density of hydrocarbon fluids. In conventional thermodynamic equations of state, each component of the fluid is specified with some characteristic parameters such as the acentric factor, critical temperature, and critical pressure. Similarly, in the Sanchez-Lacombe equation of state each component has some characteristic parameters which are obtained for pure components. Since there are no correlations for plus fractions (unknown fractions), the aim of this study is to present empirical correlations to predict the characteristic parameters of plus fractions based on experimental data. These empirical correlations are then used so that the Sanchez-Lacombe equation of state can be applied to determine the liquid phase density of hydrocarbon fluids.